The Contribution of an Ecological and Environmentalist Association to the Teaching of Sciences in de Jaciara: limits and possibilities (Research, Society and Development, 2019)
This research aims to understand the contribution of AEMA - Ecological Association and Environmental Environment - located at Avenida Pajé, s / n, Bosque Augusto Ruschi, Centro, Jaciara - MT in the sense of providing an alternative of practical and reflective teaching of Sciences and, as such, to diffuse the environmental culture through the elementary schools of the municipality of Jaciara-MT. This Ecological Association is non-profit and exclusively associative, cultural and technical-scientific of protection and recovery of the environment, being able to collaborate with other similar associations, in addition to extend its actions to other municipalities, whenever requested, thus minimizing damages environmental impacts in the region. The methodological and technical procedures adopted to develop this scientific research, aiming to achieve the proposed objective, are qualitative, using a case study, in addition to an exhaustive search through bibliographic surveys, reading of EEA documents, visits and interviews. The results achieved allow a new way of working the science discipline, so that the practice becomes responsible and sustainable actions, thus spreading an environmental culture in the society of the São Lourenço Valley.